Integrating javanese ethnomathematics approaches into the geometry learning of junior high school - Pardimin, Pardimin; Supriadi, Didi (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2025)
This study explores mathematics teachers’ perceptions regarding the integration of Javanese ethnomathematical approaches into geometry instruction at the junior high school level. The research involved mathematics teachers from 12 junior high schools across three provinces in Indonesia: DI Yogyakarta, Central Java, and East Java. Data were gathered through a structured survey instrument designed to assess opinions on the ethnomathematics-based model, supplemented by Focus Group Discussions to capture user evaluations. Descriptive analysis was employed to examine the collected data. The findings indicate that teachers hold a positive perception toward the use of ethnomathematics in geometry learning. This perception is reflected in several aspects, including awareness, prior exposure, evaluation of instructional design and implementation, practical use in teaching, and student assessment. The integration of Javanese ethnomathematics is deemed reasonably acceptable, particularly in terms of its introduction, content, evaluation mechanisms, and closing components. These findings offer practical insights for culturally responsive mathematics education that embraces local wisdom in classroom practice.